1994
DOI: 10.1104/pp.105.4.1089
|View full text |Cite
|
Sign up to set email alerts
|

Ozone-Induced Expression of Stress-Related Genes in Arabidopsis thaliana

Abstract: Ozone is a major gaseous pollutant that is known to have detrimental effects on plant growth and metabolism. We have investigated the effects of ozone on Arabidopsis fhaliana growth and the pattern of expression of several stress-related genes. A. thaliana plants treated with either 150 or 300 parts per billion (ppb) ozone daily for 6 h exhibited reduced growth and leaf curling.Fresh and dry weights of ozone-treated plants were reduced 30 to 48% compared to ambient air controls. RNA blot analyses demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
110
2
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(130 citation statements)
references
References 29 publications
17
110
2
1
Order By: Relevance
“…O 3 -induced leaf yellowing in Arabidopsis was previously observed in older leaves exposed to O 3 continuously for 2 d (Kubo et al, 1995). Rosette growth was reduced and downward leaf curling was evident within 4 d of O 3 exposure, similar to results obtained by Sharma and Davis (1994) and Rao et al (1995). Leaf curling appeared to be an altered growth response and was not the result of dehydration, since the percent dry matter did not vary between treatments in an independent experiment (data not shown).…”
Section: Discussionsupporting
confidence: 82%
“…O 3 -induced leaf yellowing in Arabidopsis was previously observed in older leaves exposed to O 3 continuously for 2 d (Kubo et al, 1995). Rosette growth was reduced and downward leaf curling was evident within 4 d of O 3 exposure, similar to results obtained by Sharma and Davis (1994) and Rao et al (1995). Leaf curling appeared to be an altered growth response and was not the result of dehydration, since the percent dry matter did not vary between treatments in an independent experiment (data not shown).…”
Section: Discussionsupporting
confidence: 82%
“…Previous research showed that mRNA for cytosolic CSD1 is induced in response to ozone fumigation (Sharma and Davis, 1994;Conklin and Last, 1995). We confirmed this observation and extended it to show that the CSD1 protein is also rapidly induced in response to ozone (Fig.…”
Section: Regulation Of Cytosolic Csd1 By Oxidative Stresssupporting
confidence: 88%
“…10A). The mRNA had decreased 24 h after the start of the fumigation to a steady-state level that was elevated compared with unfumigated controls, similar to the results seen by Sharma and Davis (1994). Although stimulated by Figure 9.…”
Section: Sod Regulation In Response To Ozone-mediated Oxidative Stresssupporting
confidence: 78%
See 1 more Smart Citation
“…It is not the first time that a delay in ozone triggering emissions has been reported. Sharma et al (1994) fumigated thaliana leaves and observed 3 h delay in the synthesis of phenylpropanoid compounds while Heiden at al. (1999) reported enhanced SQT concentrations 5 h after fumigating an ozone resistant variety of Nicotiana tabacum with 170 nmol mol −1 O 3 .…”
Section: Discussionmentioning
confidence: 97%